The Contribution of Cooperatives to the Indonesian Economy - Noviami Trisniarti; Nanda Nur Sofyana; Azhari Azhari (Almana : Jurnal Manajemen dan Bisnis, 2022)
The number of cooperatives in Indonesia reaches hundreds of thousands, but 40% of cooperatives in Indonesia are not active for various reasons. This study aims to evaluate descriptively the contribution of cooperatives in the Indonesian economy, especially in terms of employment and economic growth. This study uses descriptive analysis using data sourced from the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia and the Central Bureau of Statistics. The results showed that as much as 9.2 % of the total population of Indonesia are members of cooperatives. The percentage of cooperatives' contribution to Indonesia's gross domestic product is still below 5%. As for employment, cooperatives are only able to absorb 0.5 % of the entire working population of Indonesia.